Member Service Quality Development Strategy Using SWOT Analysis Study on Bhina Raharja Savings and Loans Cooperative in Rembang Regency - Arif Darmawan; Mamik Indaryani; Dwi Soegiarto (LP2M IAIN Palopo, 2026)
This study aims to analyze service quality at the Bhina ​​Raharja Savings and Loan Cooperative in Rembang Regency using the 8P marketing mix framework and SWOT analysis. The study uses a qualitative approach. Data were collected through observation, in-depth interviews with five informants consisting of managers, service officers, and members, as well as supporting document studies. The results of the study found four main themes, namely the spirit of kinship as a relational strength based on trust but not yet standardized in written SOPs, the convenience and accessibility of physical services that are quite good but not yet integrated with digital services, the transparency of costs that are not fully understood by members, and the need for digital modernization as both an opportunity and a challenge for organizational adaptation. The SWOT analysis shows that the strengths lie in social capital and emotional closeness, while the weaknesses lie in manual systems, limited standardization, and cost communication. Opportunities stem from the trend of digitalization and community economic awareness, while threats come from fintech and digital banking. Recommended strategies include humanistic digital transformation, increased cost transparency, revitalization of human resource competencies, and optimization of service facilities. Improving service quality requires a balance of family values, transparency, and technological innovation to strengthen loyalty and competitiveness in cooperatives.